2018
DOI: 10.1039/c8ra05621h
|View full text |Cite
|
Sign up to set email alerts
|

The stability and bioaccessibility of fucoxanthin in spray-dried microcapsules based on various biopolymers

Abstract: Fucoxanthin is a major marine carotenoid with many biological activities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(31 citation statements)
references
References 46 publications
(56 reference statements)
2
24
1
Order By: Relevance
“…They confirmed that the degradation of carotenoids was best described by first‐order kinetic model. Although, on contrary to our findings, Sun et al () found the second‐order kinetic model for describing thermal degradation of fucoxanthin microencapsulated by various coating agents.…”
Section: Resultscontrasting
confidence: 99%
See 1 more Smart Citation
“…They confirmed that the degradation of carotenoids was best described by first‐order kinetic model. Although, on contrary to our findings, Sun et al () found the second‐order kinetic model for describing thermal degradation of fucoxanthin microencapsulated by various coating agents.…”
Section: Resultscontrasting
confidence: 99%
“…Moreover, Wang, Lu, Lv, and Bie () achieved approximately 91.6% encapsulation efficiency when curcumin was encapsulated inside the mixture of PS and gelatin. In another report, Sun et al () presented the high encapsulation efficiency of fucoxanthin encapsulated by MD (92.35%) and GA (86.48%) alone. Based on these findings, it appears that the combined MD and GA are more appropriate to meet the requirement of food industries.…”
Section: Resultsmentioning
confidence: 94%
“…Fucoxanthin enclosed in microcapsules with palm stearin as the solid lipid core is more stable in light, high humidity, and elevated temperature than free fucoxanthin. These forms of biological encapsulation can effectively protect fucoxanthinin the acid environment of the stomach and increase the release of fucoxanthin in the intestine [ 19 ]. Encapsulation represents a novel and attractive development, establishing a satisfactory oral delivery system to increase the bioavailability of fucoxanthin, thus expanding its application and convenience of administration.…”
Section: Different Sources Of Fucoxanthin and Stability Improvemenmentioning
confidence: 99%
“…The unique chemical characteristics of fucoxanthin (unusual allenic bond, epoxide group, and conjugated carbonyl group within a polyene chain) ( Figure 1) confer several oxidation targets to this molecule. The main factors that can trigger carotenoids degradation are oxygen, light, high temperatures, enzymatic reactions, heavy metals exposure, and extended periods of storage [74][75][76][77][78][79]. Different studies have evaluated the stability of fucoxanthin in terms of temperature when freely added to diverse matrixes.…”
Section: Free Moleculementioning
confidence: 99%
“…A study evaluated up to six ingredients to microencapsulate fucoxanthin: hydroxypropyl-β-cyclodextrin, maltodextrin, gum Arabic, whey protein isolate, isolated pea protein and gelatin. After exposing microcapsules to a temperature of 90 • C for 24 h, those built with whey protein isolate, gum Arabic, and maltodextrin displayed the lower degradation rates with values of 38%, 44% and 45%, respectively [76]. Another work utilized nanogels prepared by ionic gelation with different amounts of chitosan and glycolipid or sodium tripolyphosphate.…”
Section: Encapsulationmentioning
confidence: 99%